Language Learning in the 21st Century: How Technology is Shaping Modern Pedagogy - Ricky Firmansyah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to examine the impact of technology on language learning in the 21st century, focusing on how technology is shaping modern pedagogy in language education. Using a Systematic Literature Review (SLR) approach, this research analyzes recent studies from the past five years on the application of technology in language learning. The findings indicate that technology, such as language learning apps, e-learning platforms, and artificial intelligence (AI), has significant benefits in enhancing basic language skills, such as vocabulary and reading comprehension. However, technology has not fully addressed challenges in developing speaking and writing skills, which require social and contextual interaction. Additionally, challenges include the lack of digital training for teachers and the digital divide that affects the quality of language education. Therefore, the integration of technology in language teaching should be accompanied by appropriate pedagogical approaches, professional training for teachers, and improved infrastructure to overcome digital inequalities. This study provides valuable insights for the development of language education policies that effectively incorporate technology.